Raman spectroscopic study on the subpicosecond dynamics in calf-thymus DNA, upon lowering the pH and in the presence of Mn2+ ions. Issue 6 (2008) - Muntean Muntean, Cristina M. Cristina M.; Bratu Bratu, Ioan Ioan
Abstract : In this paper the Raman total half bandwidths of calf-thymus DNA vibrations have been measured as a function of pH (3.45–6.4), in the presence of Mn 2+ ions, respectively. The dependencies of the half bandwidths and of the global relaxation times, on DNA molecular subgroup structure and on pH, are reported. It is shown that changes in the subpicosecond dynamics of molecular subgroups in calf-thymus DNA can be monitored with Raman spectroscopy. Particularly, the Raman band parameters for the vibrations at 728 cm –1 (dA), 787 cm –1 (dC), 1093 cm –1 (PO2 – ), 1376 cm –1 (dA, dG, dT, dC), 1489 cm –1 (dG, dA) and 1578 cm –1 (dG, dA) of MnDNA complexes, at reduced and low pH values, are presented. In our study, the full widths at half-maximum (FWHM) of the bands in calf-thymus DNA are typically in the wavenumber range from 11 to 27 cm –1 . It can be observed that the molecular relaxation processes studied in this work, have a global relaxation time smaller than 0.965 ps and larger than 0.393 ps. The limit values are characteristic for dA and dC residues, respectively (vibrations at 728 and 787 cm –1 ). Low pH-induced melting of double helical structure in calf-thymus DNA, in the presence of Mn 2+ ions, results for some bands in smaller global relaxation times, and larger bandwidths, respectively, as a consequence of the increased interaction of the base moieties with the solvent molecules. This behaviour is most evident for the bands at 787 cm –1 up to pH 3.8, at 1578 cm –1 up to pH 3.45 and is partially confirmed for the DNA backbone PO2 – symmetric stretching vibration at 1093 cm –1 . The fastest molecular dynamics was obtained for the adenine band at 728 cm –1 in the pH interval 3.45–3.8 (global relaxation time 0.885 ps), for the cytosine ring breathing mode near 787 cm –1 around the pH 3.8 (global relaxation time 0.393 ps), for the band at 1093 cm –1 in the pH interval 3.8–4.4 (global relaxation time 0.518 ps) and for the vibration near 1578 cm –1 at pH 3.45 (global relaxation time 0.544 ps). A comparison between different time scales of the vibrational energy transfer processes, characterizing the protonated MnDNA structural subgroups has been given. We have found that metal ion's type and concentration are modulators for the (sub)picosecond dynamics of protonated DNA molecular subgroups.